Elementary School Teachers Perceptions toward Teaching Reproductive Material as Part of Science Education in Elementary Schools - Iskandar, Suhendra (Jurnal Pijar Mipa, 2025)
Teaching reproductive education at the elementary school level remains a sensitive issue, balancing the need to prevent sexual abuse through proper knowledge with concerns about social, religious, and cultural norms. This study aims to explore the perceptions of prospective elementary school teachers in Gorontalo regarding reproductive content in science education. Using a descriptive quantitative design, data were collected from 60 respondents through a closed-ended questionnaire. The findings show that while most respondents opposed teaching reproductive material at the elementary level due to moral and cultural concerns, many were not against the content itself but rather the method of delivery and the consideration of children’s maturity. This suggests that reproductive education could be implemented if presented through contextual and values-based approaches, such as moral-educational narratives. The study highlights both the sensitivity of the topic and the potential pathways for its gradual and culturally aligned integration into science education.